PRODUCTION OF 18F- LABELLED COMPOUNDS COMPRISING HYDROLYTIC DEPROTECTION STEP AND SOLID PHASE EXTRACTION - WOUTERS, LUDOVIC; LIGNON, STEVE (2013)
The present invention provides a simplified method for the preparation of F-labelled compounds that is particularly suitable for automation. The method of the invention is specifically applicable where the 18F-labelled compound is prepared from a labelling precursor that comprises protecting groups and wherein the synthetic route to the final compound includes removal of these protecting groups by acid or alkaline hydrolysis. Also provided by the present invention is a cassette useful for carrying out the method of the invention in an automated manner. L'invention concerne un procédé de préparation simplifié de composés étiquetés F qui est particulièrement approprié pour une automatisation. Le procédé de l'invention s'applique spécifiquement lorsque le composé étiqueté 18F est préparé à partir d'un précurseur d'étiquetage qui comprend des groupes de protection et dans lequel la voie de synthèse jusqu'au composé final comprend l'élimination de ces groupes de protection par hydrolyse acide ou alcaline. L'invention concerne également une cassette utilisée pour mettre le procédé en oeuvre de manière automatique.